Pengaruh Model Pembelajaran Inside-Outside Circle terhadap Hasil Belajar pada Mata Pelajaran Fiqih di Mts Al-Bukhary Sreseh Sampang - Ike Noer Jannah; Moh. Isbir (Jurnal Subulana, 2021)
This article aims to determine the effect of the Inside-Outside Circle learning model on learning outcomes in Islamic Civilization History subjects at MTs Al-Bukhary Sreseh Sampang. This research is a quantitative research type Pre Experimental Design. The subjects in this study were all students at MTs Al-Bukhary. The research sample was class VIIIa as the experimental class with the Inside-Outside Circle learning model and class VIIIb as the control class with the lecture learning method. The instrument used in this study was an essay question. The data analysis technique used the normality test with the chi square test followed by hypothesis testing with the t test. The results showed that the implementation of learning using the Inside-Outside Circle learning model was very helpful in improving the learning outcomes of Islamic Civilization History at MTs Al-Bukhary. Based on the results of the analysis and discussion of the research data, it is obtained that the hypothesis test results have a greater t test result of -15,339 than learning without using the Inside Outside Circle learning model of -11,306. Thus it can be concluded that Ha is accepted, meaning that there is an influence of the Inside-Outside Circle learning model on learning outcomes in Islamic Civilization History subjects at MTs Al-Bukhary Sreseh Sampang. Keyword : Inside-Outside Circle, Learning Outcome